ANALISA HUBUNGAN INTENSITAS PERSAINGAN, UKURAN PERUSAHAAN, ORGANISASI PEMBELAJARAN DENGAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA SEKTOR RESTORAN DI SURABAYA - Omar, Setiawan (Business Accounting Review, 2013)
Increased economic growth Surabaya especially in the restaurant, making the competition even more increase. For that businesses of today need enough information to solve the existing competition and use it in decision control. Therefore researchers interested in studying the relationship between the intensity of competition, firm size, and organizational learning and the use of accounting information systems in restaurant sector. AIS at the restaurant used to support the daily activities as well as in corporate decision-making, and therefore to see the high level of competition and the companys desire to increase the size of his company, AIS became the company needs in order to help the decision-makers to take the right and accurate because based on the rational information. Beside that AIS can be useful to help AIS restaurants to learn the organization that can be useful an organizational memory. The data show that the AIS at many restaurants use to support the daily activities. Data were obtained through questionnaires distributed to 89 manager and 11 owner of a restaurant in Surabaya. The data is processed using the product moment correlation. The results showed that the variables of intensity of the competition, firm size, and organizational learning have a significant relationship with the use of AIS.